Evidence for the first multi-species shark nursery area in Atlantic Africa (Boa Vista Island, Cabo Verde) - Rosa, Rui; Nunes, Emanuel; Pissarra, Vasco; Santos, Catarina Pereira; Varela, Jaquelino; Baptista, Miguel; Castro, Joana; Paula, José Ricardo; Repolho, Tiago; Marques, Tiago A.; Freitas, Rui; Frazão Santos, Catarina (Frontiers in Marine Science, 2023)
This study describes the first potential multi-species shark nursery area in Atlantic Africa (Sal Rei Bay – SRB, Boa Vista Island, Cabo Verde). From August 2016 to September 2019, 6162 neonates and juveniles of 5 different shark species were observed in SRB using beach gillnet-based bycatch surveys, namely milk (Rhizoprionodon acutus; n= 4908), scalloped hammerhead (Sphyrna lewini; n= 1035), blacktip (Carcharhinus limbatus; n=115), Atlantic weasel (Paragaleus pectoralis; n= 93) and nurse (Ginglymostoma cirratum; n= 12) sharks. Except for nurse sharks, significant seasonal variations in shark relative abundance were observed, with higher levels being recorded during summer and autumn. These findings, together with local knowledge (interviews to fishermen), denote the consistent use of SRB by juvenile sharks and its preference relative to other areas in the region. Ensuring the protection and conservation of SRB nursery area is especially relevant as, according to IUCN, all identified shark species are threatened with extinction over the near-future – in particular, scalloped hammerheads (critically endangered) and Atlantic weasel sharks (endangered). The effective protection of SRB will not only support the conservation of shark populations, but also of other charismatic fauna (e.g., loggerhead turtles) and broader benthic and pelagic ecosystems.